2004
DOI: 10.1037/0022-3514.86.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Effects of Anger and Happiness in Negotiations.

Abstract: Three experiments investigated the interpersonal effects of anger and happiness in negotiations. In the course of a computer-mediated negotiation, participants received information about the emotional state (anger, happiness, or none) of their opponent. Consistent with a strategic-choice perspective, Experiment 1 showed that participants conceded more to an angry opponent than to a happy one. Experiment 2 showed that this effect was caused by tracking--participants used the emotion information to infer the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
829
6
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 709 publications
(898 citation statements)
references
References 100 publications
55
829
6
8
Order By: Relevance
“…The idea that communicated emotions may convey certain intentions which one may subsequently take into account for one's own actions has been convincingly demonstrated by Van Kleef, De Dreu and Manstead (2006;see also De Cremer, Wubben, & Brebels, in press;Sinaceur & Tiedens, 2006;Van Kleef, De Dreu, & Manstead, 2004). These authors showed that when a negotiation opponent communicated guilt, people were unlikely to concede because they expected their opponent to be willing to make up for his or her tough demands that were offered in previous rounds (Van Kleef et al, 2006).…”
Section: Emotional Displays In Social Dilemmasmentioning
confidence: 96%
“…The idea that communicated emotions may convey certain intentions which one may subsequently take into account for one's own actions has been convincingly demonstrated by Van Kleef, De Dreu and Manstead (2006;see also De Cremer, Wubben, & Brebels, in press;Sinaceur & Tiedens, 2006;Van Kleef, De Dreu, & Manstead, 2004). These authors showed that when a negotiation opponent communicated guilt, people were unlikely to concede because they expected their opponent to be willing to make up for his or her tough demands that were offered in previous rounds (Van Kleef et al, 2006).…”
Section: Emotional Displays In Social Dilemmasmentioning
confidence: 96%
“…& Van Beest, 2008;Van Kleef et al, 2004a), whereas they infer from expressions of happiness that the counterpart is lenient and easily satisfied (Van Dijk et al, 2008;Van Kleef et al, 2004a). Other work provided evidence that deviant group members infer from their fellow group members' expressions of anger versus happiness that their fellow group members reject versus accept them, respectively (Heerdink et al, 2013, Heerdink, Van Kleef, Homan, & Fischer, 2015.…”
Section: Social Effects Of Emotions Across Expressive Modalitiesmentioning
confidence: 99%
“…Specifically, the review provided support for the notion put forward in EASI theory that emotional expressions across expressive channels influence observers' affective, inferential, and behavioral responses. With regard to affective responses, one robust finding across numerous studies is that expressions of happiness engender positive affective reactions in observers, such as reciprocal feelings of happiness, positive affect, and/or positive impressions of the expresser (e.g., Barsade, 2002;Sy et al, 2005;Van Kleef et al, 2004a;Van Kleef et al, 2009), whereas expressions of anger engender negative affective responses, such as reciprocal feelings of anger, negative affect, and/or negative impressions of the expresser (e.g., Barsade, 2002;Friedman et al, 2004;Kopelman, Rosette, & Thompson, 2006;Lewis, 2000;Sy et al, 2005;Van Kleef et al, 2004a;Van Kleef et al, 2009). Important to note, these effects occurred across different expressive modalities, and no systematic effects of expressive modality were observed.…”
Section: Social Effects Of Emotions Across Expressive Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Study 1: Power Decreases Trust in a Negotiation Task Study 1 used an established negotiation task (34,35), in which participants were asked to negotiate over a consignment of cell phones. All participants were assigned to the role of seller and were provided with a payoff chart showing the points allocated to them for different combinations of price, warranty period, and service contract duration.…”
Section: Significancementioning
confidence: 99%